A new Palearctic species of the genus Gonempeda Alexander, 1924 (Diptera: Limoniidae) - Pilipenko, Valentin (Zootaxa, 2017)
A new species of Gonempeda from Caucasus is described and illustrated. Gonempeda flava (Schummel, 1829) is recorded from Russia for the first time. An identification key of all Palearctic Gonempeda is presented.